Peripheral nervous system: A promising source of neuronal progenitors for central nervous system repair - Mueller, Jessica L.; Stavely, Rhian; Hotta, Ryo; Goldstein, Allan M. (Frontiers in Neuroscience, 2022)
With a steadily aging population there is an increasing prevalence of neurological disorders. Given the lack of effective treatment strategies and a limited ability for the central nervous system (CNS) to regenerate endogenously, there is a critical need to better understand exogenous strategies for nervous system repair. Stem cell therapy offers a promising approach to promote the repair of neurologic tissue and function, however studies to date have been limited by various factors including challenges in harvesting donor cells from the CNS, ethical concerns regarding use of embryonic or fetal tissue, tumorigenic potential of induced pluripotent stem cells, and immune-mediated rejection of non-autologous cell sources. Here we review and propose two alternative sources of autologous cells derived from the peripheral nervous system (PNS) for CNS repair: enteric neuronal stem cells (ENSCs) and neural crest-derived Schwann cells found in subcutaneous adipose tissue (termed SAT-NSCs). ENSCs can be successfully isolated from the postnatal enteric nervous system, propagated in vitro, and transplanted successfully into models of CNS injury via both direct intracerebral injection and systemic tail vein injection. Similarly, SAT-NSCs can be readily isolated from both human and mouse adipose tissue and, although not yet utilized in models of CNS injury, have successfully been transplanted and restored function in models of colonic aganglionosis and gastroparesis. These unique sources of PNS-derived autologous cells offer an exciting option for stem cell therapies for the CNS as they have proven neurogenic potential and eliminate concerns around tumorigenic risk, ethical considerations, and immune-mediated rejection.